Office space [videorecording (DVD)] - Judge, Mike; Livingston, Ron; Root, Stephen; Cole, Gary, 1956-; McGinley, John C.; Herman, David, 1967 February 20-; Naidu, Ajay; Aniston, Jennifer; Suhrstedt, Tim; Frizzell, John, 1966- (20th Century Fox Home Entertainment, 2018)
When white-collar peon Peter Gibbons decides he's had enough and neglects his job, he is quickly promoted to upper management.